MODEL PENDEKATAN KEN BLANCHARD PADA TEMA 5 PAHLAWANKU DALAM MENINGKATKAN KARAKTER SISWA - Karimah, Via Haiyun; Ramadhan, Tomi; Hardiyana, Minati Rina; Pradana, Dhimas Rega; Istiningsih, Istiningsih (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
The revolution era 4.0 has helped humans a lot in running the wheels of life, but there have also been some unfavorable impacts that have emerged in this era. One of the affected sectors is the education sector. The condition of students character in the era of the industrial revolution 4.0 is currently very concerning, making educators not only teach theory but also how students practice it in everyday life.Â  Educators must be sensitive to how to maintain and improve the character values of students. This study's goal is to explain how Ken Blanchard's situational leadership theory and delegation model can improve student character in class 4 theme 5 Pahlawanku. This study uses a literature study approach (Library Research) by analyzing international and national articles that have strong relevance to the concepts in this research. So the results of this study indicate that the Ken Blanchard approach model with a delegation pattern can improve student character in the form of proactivity, responsibility, independence, problem solving, and creativity.